Magnetohydrodynamics (MHD) flow of ternary nanofluid and heat transfer past a permeable cylinder with velocity slip - Hussein, Umi Nadrah; Khashi'ie, Najiyah Safwa; Arifin, Norihan Md; Pop, Ioan (Elsevier B.V., 2025)
The increasing demand for energy-efficient and environmentally sustainable solutions has driven the exploration of ternary nanofluids for enhanced heat transfer applications. This numerical study investigates the magnetohydrodynamics (MHD) flow and heat transfer characteristics of a ternary hybrid nanofluid (copper-alumina-titania/water) over a shrinking/stretching cylinder, considering the effects of velocity slip, suction, and curvature parameters. The variable wall temperature is also included in the physical model. The model in PDEs is transformed into a simplified version of differential equations (ODEs) which can be solved using the bvp4c solver. Validation against previously published data confirms the accuracy of the model. Two solutions are possible if the shrinking surface is permeable (with suction effect), while only a unique solution is for the stretching case. Surprisingly, the copper-alumina-titania/water exhibits a lower heat transfer rate but higher skin friction as compared to the copper-alumina/water. Specifically, the heat transfer coefficient decreases by 5-10 % when incorporating the titania nanoparticle, while an increase of 8-12 % for the skin friction coefficient. Additionally, the velocity slip and curvature parameters accelerate the boundary layer separation, whereas increased suction delays this process. These findings provide insights into optimizing thermal management systems using ternary hybrid nanofluids, particularly under MHD effect.